Regularized lattice Boltzmann multicomponent models for low capillary and Reynolds microfluidics flows. (15th May 2018) - Montessori, Andrea; Lauricella, Marco; La Rocca, Michele; Succi, Sauro; Stolovicki, Elad; Ziblat, Roy; Weitz, David
Highlights: A regularized color gradient LB model for multicomponent flows is presented. The model is employed to simulate microfluidic devices (focusing devices and step emulsifiers). Preliminary 3D simulations of an alternative step emulsifier device have been presented. Abstract: We present a regularized version of the color gradient lattice Boltzmann (LB) scheme for the simulation of droplet formation in microfluidic devices of experimental relevance. The regularized version is shown to provide computationally efficient access to capillary number regimes relevant to droplet generation via microfluidic devices, such as flow-focusers and the more recent microfluidic step emulsifier devices.